KETERLIBATAN DAN KEMAMPUAN TEKNIK PERSONAL PADA EFEKTIVITAS PENGGUNAAN SISTEM INFORMASI AKUNTANSI - Wilayanti, Ni Wayan; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi; Vol 15 No 2 (2016), 2016)
This research was conducted to determine the effect of personal involvement and engineering capabilities in the effective use of Accounting Information Systems (AIS) with education and training as moderating the LPD District Tegallalang. Sampling technique used is the technique of non-probability sampling with purposive sampling method in order to obtain a sample of 60 samples. Sampling technique used is the technique of non-probability sampling with purposive sampling method in order to obtain a sample of 60 samples. Data collected by using a survey method, which is spread kuersioner the LPD employees in District Tegallalang. The data analysis technique used is Moderated Regression Analysis (MRA). Based on the results of the analysis indicate that the involvement and engineering capabilities of personal influence on the effectiveness of the use of AIS. The results also showed that moderate the influence of education and training and engineering capabilities of personal involvement on the effectiveness of the use of AIS.
Keywords: Effectiveness SIA usage, involvement, technical capabilities, education and training